2006
DOI: 10.1007/s11104-006-9111-6
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium induces premature xylogenesis in barley roots

Abstract: The effect of Cd on H 2 O 2 production, peroxidase (POD) activity and root hair formation were analyzed in barley root. Cd causes a strong H 2 O 2 burst in the root region 0-6 mm behind the root tip. POD activity was activated in root tip and raised toward the root base in Cd treated roots. In situ analyses showed that both elevated H 2 O 2 production and POD activity are localized in the early metaxylem vascular bundles. Cd induces root hair formation in the region 2 to 4 mm behind the root tip that was not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…and Dŭrčeková et al . [18,19], it is probable that Cd inhibited main root growth as a consequence of Cd-stimulated premature root differentiation and development, involving xylogenesis, induction of lateral roots, and growth of lateral roots and root hairs. The increase in lateral root diameter (Table 1 and Figure 2C) could be a consequence of Cd-induced xylogenesis, that act as a barrier to protect root from Cd, while the increasing of root branching could be considered as an “escaping” strategy of the roots in order to find areas free of Cd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Dŭrčeková et al . [18,19], it is probable that Cd inhibited main root growth as a consequence of Cd-stimulated premature root differentiation and development, involving xylogenesis, induction of lateral roots, and growth of lateral roots and root hairs. The increase in lateral root diameter (Table 1 and Figure 2C) could be a consequence of Cd-induced xylogenesis, that act as a barrier to protect root from Cd, while the increasing of root branching could be considered as an “escaping” strategy of the roots in order to find areas free of Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable effort has also been directed at clarifying the processes and factors contributing to IAA and CK homeostasis during Cd exposure, but the entire picture remains to be elucidated, as the synthesis of these hormones is regulated in response to different and complex signaling pathways [17]. Moreover, with the exception of some studies [16,18,19], the action of IAA and CKs on root morphology and architecture in Arabidopsis has not been deeply examined.…”
Section: Introductionmentioning
confidence: 99%
“…Kristensen et al (1997) suggested that PRX8 participates in the deposition of phenolic compounds in papillae during fungal infection, while its constitutive expression in transgenic tobacco leads to growth retardation as a result of elevated PRX activity and lignification. Recently, we have reported that Cd caused premature root development involving xylogenesis and root hair formation, which is correlated with a shortening of the root elongation zone and therefore with root growth reduction (Durčeková et al, 2007). PRX8 is a good candidate for participation in the processes of lignification during xylogenesis in the barley root.…”
Section: Discussionmentioning
confidence: 99%
“…Typical toxic effects of Cd on plants are the inhibition of primary root growth and increased lateral root density (Hu et al, 2013). Although the influence of Cd on root hairs has not been researched in detail, studies have shown that Cd at specific concentrations (that inhibit root growth by about 50%) increases root hair density and length in various plant species including radish (Vitoria et al, 2003), barley (Durcekova et al, 2007), sorghum (Kuriakose and Prasad, 2008), and Rhode grass (Kopittke et al, 2010). However, the molecular mechanism of root hair enhancement in response to Cd and As has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%